2012
DOI: 10.1590/s0103-05822012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Valores de referência e fatores relacionados à mobilidade torácica em crianças brasileiras

Abstract: Valores de referência e fatores relacionados à mobilidade torácica em crianças brasileirasValores de referencia y factores relacionados con la movilidad torácica en niños brasileños Raphaella Oliveira E. da ABSTRACTObjective: To provide reference values and to evaluate the factors influencing thoracic mobility in children aged 7 to 11 years old.Methods: A total of 166 children were assessed from public and private schools (90 girls and 76 boys) in the city of Natal (Northeast Brazil). Demographic and anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…According to the study, "Thoracic mobility is related to the integrity of the respiratory muscles, which assists in the expansion and retraction of the thoracic cavity. " 20 This measure is used to "assess parameters such as thoracic amplitude, lung volumes and capacities, lung compliance, thoracoabdominal mechanics, diaphragmatic function, muscle work and dyspnea. " 20 "Chest mobility and lung function may change not only with the growth and appearance of respiratory diseases, but also with other factors such as body composition, sex, age, height, and ethnicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the study, "Thoracic mobility is related to the integrity of the respiratory muscles, which assists in the expansion and retraction of the thoracic cavity. " 20 This measure is used to "assess parameters such as thoracic amplitude, lung volumes and capacities, lung compliance, thoracoabdominal mechanics, diaphragmatic function, muscle work and dyspnea. " 20 "Chest mobility and lung function may change not only with the growth and appearance of respiratory diseases, but also with other factors such as body composition, sex, age, height, and ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…20 This measure is used to "assess parameters such as thoracic amplitude, lung volumes and capacities, lung compliance, thoracoabdominal mechanics, diaphragmatic function, muscle work and dyspnea. " 20 "Chest mobility and lung function may change not only with the growth and appearance of respiratory diseases, but also with other factors such as body composition, sex, age, height, and ethnicity. 20 The research demonstrated significance between the presence of primitive reflexes and the gestational age of 38 to 42 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, this respiratory discomfort is evaluated through the number of respiratory incursions and the quality of thoracic expandability, the lower the thoracoabdominal mobility and the greater the respiratory rate, the worse the clinical condition of the newborn 5,7 . However, in clinical practice, noninvasive methods capable of quantifying respiratory evolution are preferable and also more reliable when compared to the subjective evaluation of the quality of thoracic expandability [8][9][10] . Considering that cesarean delivery can be a difficult factor in the respiratory evolution of newborns and that thoracoabdominal mobility is directly related to the clinical condition of the newborn, the present study aims to evaluate the impact of the type of delivery on the thoracic and abdominal mobility in newborns (NBs).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…The use of photogrammetry for the analysis of respiratory movement allows establishing evidence related to thoracic and abdominal kinetics, this information can be used to infer respiratory mechanical behavior even in patients who do not voluntarily control respiration, as in newborns [8][9][10][11][12] . However, some limitations should be considered.…”
mentioning
confidence: 99%